The role of comorbidity in the development of Long-COVID - T.V. Chernii; V.I. Chernii; D.A. Fokina (Infusion & Chemotherapy, 2023)
BACKGROUND. Post-COVID syndrome is a set of conditions that occur in patients after a coronavirus infection. To date, there remains great interest in identifying the relationships between the influence of concomitant diseases on the course of SARS-CoV-2 infection and the selection of a justified treatment regimen from the point of view of the pathogenesis of the formation of long-term consequences of the disease.